The Effectiveness of Sepak Takraw Smash Skills Through Drill Training Methods in High School Student Athletes - Saiful Saiful; Ramli Ramli; Ahmad Rum Bismar; Muh. Adnan Hudain; Suriah Hanafi (ETDC: Indonesian Journal of Research and Educational Review, 2026)
Smashing skills are a crucial element in achieving success in sepak takraw. However, many student-athletes at the regional level, particularly in Maros Regency, have not mastered this technique optimally due to repetitive and less varied training methods. This study aims to evaluate the effectiveness of the drill training method in improving smash skills among high school sepak takraw athletes. This research employed a quasi-experimental approach with a pretest–posttest control group design. A sample of 20 high school athletes was selected using purposive sampling and divided into an intervention group (n=10) and a control group (n=10). The instrument used was a standardized smash skills test. After a 4-week training program, paired sample t-tests were used to look at changes within groups and independent t-tests were used to look at differences between groups. The findings revealed a significant improvement in the intervention group’s performance. The average score increased from 21.30 in the pretest to 33.60 in the posttest (a gain of 12.30 points). Statistical analysis yielded a p-value (Sig. 2-tailed) of 0.000 < 0.05, confirming that the drill method is highly effective. The drill training method significantly enhances the smash skills of high school sepak takraw athletes. This study suggests that coaches should implement structured drill programs to optimize technical performance in school-based sports development.